2009
DOI: 10.1158/1078-0432.ccr-08-3012
|View full text |Cite|
|
Sign up to set email alerts
|

MSH6 Mutations Arise in Glioblastomas during Temozolomide Therapy and Mediate Temozolomide Resistance

Abstract: Purpose: Over the past few years, the alkylating agent temozolomide has become the standardof-care therapy for patients with glioblastoma, the most common brain tumor. Recently, largescale cancer genome sequencing efforts have identified a hypermutation phenotype and inactivating MSH6 mismatch repair gene mutations in recurrent, post-temozolomide glioblastomas, particularly those growing more rapidly during temozolomide treatment. This study aimed to clarify the timing and role of MSH6 mutations in mediating g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
277
2
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(305 citation statements)
references
References 33 publications
21
277
2
5
Order By: Relevance
“…13 Additional in vivo and in vitro studies provided evidence that MSH6 mutations are selected for during TMZ treatment and may thus be causally associated with TMZ resistance and glioblastoma relapse. 12 Other authors confirmed MSH6 alterations, 14 while high-level microsatellite instability was absent in recurrent glioblastomas. 12,14 Here, we report on a translational study performed within the framework of the German Glioma Network (GGN).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…13 Additional in vivo and in vitro studies provided evidence that MSH6 mutations are selected for during TMZ treatment and may thus be causally associated with TMZ resistance and glioblastoma relapse. 12 Other authors confirmed MSH6 alterations, 14 while high-level microsatellite instability was absent in recurrent glioblastomas. 12,14 Here, we report on a translational study performed within the framework of the German Glioma Network (GGN).…”
mentioning
confidence: 81%
“…13 A follow-up study confirmed the presence of MSH6 mutations in post-treatment TCGA glioblastomas but not in the matched pretreatment tumors. 12 Interestingly, recurrent glioblastomas do not display high-level microsatellite instability despite the presence of mutations in MSH6 and other MMR genes. 12,14 We compared the expression of MLH1, MSH2, MSH6 and PMS2 proteins in primary and recurrent glioblastoma tissues and in line with previous studies 11 detected lower expression of MSH6 in a substantial fraction of recurrent when compared to primary glioblastomas.…”
Section: Clinical Implications For Mgmt Promoter Methylation Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Selection for loss of mismatch repair proteins, such as MSH6, could be involved in a minority of patients. [51][52][53] In vivo evidence for the direct involvement of MGMT in the response of glioblastoma to alkylating agents has been provided by The Cancer Genome Atlas. 54 The value of temozolomide in the setting of recurrent glioblastoma, including its relationship with MGMT promoter methylation status, must now to be determined in patients who have already been exposed to temozolomide in the first-line setting, 55,56 as is being pursued in the DIRECTOR trial (http://clinicaltrials.gov, NCT00941460).…”
Section: The Role Of Mgmt In Glioma Subtypes Glioblastomamentioning
confidence: 99%
“…Moreover, residual tumors generally recur as more aggressive, refractory, and lethal; likely due to the inability of chemotherapy to eliminate CSC, and resulting in additional mutations accumulated in these cells during exposure to genotoxic drug regimens. 45 Genetically engineered mouse models (GEMMs) are also popular models through which tumor biology is studied. Unfortunately, these tumor models also have their intrinsic shortcomings.…”
Section: Traditional Models Have Not Predicted Clinical Successmentioning
confidence: 99%